Peningkatan Keterampilan Membaca Pemahaman melalui Model Flipped Classroom di SD N 01 Sidomulyo - Septiningrum, Eka Setya; Reffiane, Fine; Karsono, Karsono (Persatuan Guru Republik Indonesia Kota Semarang, 2021)
The objectives of this study are to: (1) improve learning outcomes on the theme of Technology Development through the Flipped Classroom model, (2) improve reading comprehension skills on the theme of Technology Development through the Flipped Classroom model, (3) increase teacher activity on the theme of Technology Development through the Flipped model. Classroom. This research is a CAR that is planned and carried out by the researchers themselves assisted by colleagues as observers which is carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection. The subjects of this study were students of Class III A SD N 01 Sidomulyo for the academic year 2020/2021 as many as 21 students. The results of this study indicate that: (1) learning outcomes on the theme of the development of Indonesian language content in terms of knowledge (KI 3) which are seen from the learning outcomes test are 90.4% in cycles 1 and 2 and reach 100% in cycle 3, from in terms of skills (KI 4) as seen from the LKPD containing Indonesian as much as 90.4% in cycle 1, 95.2% in cycle 2, and reaching 100% in cycle 3. (2) Reading comprehension skills on the theme of Technological Development refer to indicators of reading comprehension skills presented by Widasari, MU (2017: 15) with details of the achievement of indicators in cycle 1 as much as 71.5%, cycle 2 as much as 85.7%, and reaching 100% in cycle 3. (3) Teacher activities using the application of the Flipped Classroom model was measured using an observation sheet on the application of the Flipped Classroom model, the results obtained in cycle 1 were 59%, cycle 2 was 74%, and cycle 3 was 87.5%. The conclusion of this study is that the application of the Flipped Classroom model can improve learning outcomes, reading comprehension skills, and teacher activities.